The Marjuman trilobite Cedarina Lochman: thoracic morphology, systematics, and new species from western Utah and eastern Nevada, USA - Adrain, Jonathan M.; Peters, Shanan E.; Westrop, Stephen R. (Zootaxa, 2009)
Cedarina schachti n. sp. from the Marjuman (Cedaria Zone) Weeks Formation of western Utah, USA, provides the first information on thoracic morphology within the genus. Its thorax is radically different from those of species of Cedaria Walcott, with which Cedarina Lochman has been classified in Cedariidae Raymond, but strikingly similar to those of plesiomorphic remopleuridoideans grouped in the paraphyletic Richardsonellinae Raymond. If Cedarina and the remopleuridoideans are genuinely related it follows that 1) Cedariidae as traditionally conceived is paraphyletic; 2) Cedarina is a plesiomorphic sister taxon of the remopleuridoideans; and 3) the remopleuridoideans are not a component of the Order Asaphida. Silicified material of a second new species, C. clevensis from the Marjuman (Crepicephalus Zone) Lincoln Peak Formation of eastern Nevada, confirms the presence of a long thoracic axial spine and provides the first information on ontogenetic development and ventral morphology within the genus.